2013
DOI: 10.2478/v10298-012-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Flight Evolution of Melolontha Melolontha L. (Coleoptera, Scarabaeidae) Species in the Central of Moldavia Conditions, Romania

Abstract: The cockhafer (Melolontha melolontha L.) is the most widespread and best known bug. It is a polyphagous bug, being harmful both in adulthood and in larva stage. The researches were conducted at Agricultural Research and Development Station (A.R.D.S.) of Secuieni, Neamţ county, Romania, and followed the evolution of adult flight, during 1993 - 2012 with a light trap help. The gatherings and records were made daily from 1 April to 31 October every year, during the observation period. Dividing the observation per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Light traps have been successfully used in the monitoring of cockchafer swarming flights (Reichholf 1979(Reichholf , 1985(Reichholf , 1993Švestka 2006, 2007Trotuş et al 2013). It became apparent that male cockchafers outnumber the females at the light trap (Reichholf 1979(Reichholf , 1985Švestka 2006, 2007, a phenomenon which was also observed in the present study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Light traps have been successfully used in the monitoring of cockchafer swarming flights (Reichholf 1979(Reichholf , 1985(Reichholf , 1993Švestka 2006, 2007Trotuş et al 2013). It became apparent that male cockchafers outnumber the females at the light trap (Reichholf 1979(Reichholf , 1985Švestka 2006, 2007, a phenomenon which was also observed in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, cockchafers were observed leaving the soil in early/mid April when mean temperatures in the upper soil layer reached 10°C, which is in close accordance with Zivanovic (1972) and Niklas (1974). On the contrary, Richter (1962) and Trotuş et al (2013) reported adult emergence at higher (12.8-17.4°C) or even lower (6.1-14.2°C) mean soil temperatures for East Germany and Romania, respectively. Differences might be due to regional adaptations of the cockchafer populations to local conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…One of the changes was the appearance of the second peak in August. The number of generations in Eastern Romania was stable for 25 years at one generation [ 9 ]; however, in the last few years, a partial second generation registered because of the temperature increases. However, these changes in insect development take place over time, with rising temperatures reported during the last few years and an increase in effective heat units, or degree–days, accumulating per day and annually above the biological thresholds [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Romania, the pest is present in all areas where corn is the main crop [ 7 ]. The larvae feed on the epidermis of the leaves and the pollen from the inflorescences, and as it passes through the larval stages, it pierces the stem, the veins of the leaves, and the cobs, consuming the grain within the cob [ 8 , 9 ]. Larval boring causes the plants to break, which makes mechanized harvesting difficult, leading to direct quantitative losses and indirectly to grain deterioration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation